Pengaruh Pelatihan Kerja Dan Kompensasi Terhadap Kinerja Pegawai Dinas Pemadam Kebakaran Dan Penyelamatan Kota Bengkulu - Marliza Ade Fitri; Herwan MDK; Indah Dwita Putri (UNIVED Press, 2023)
This research is based on the importance of employee performance in achieving agency goals. Factors that can affect the performance of these employees include job training and compensation. The purpose of this study is to find out whether there is an effect of job training and compensation on whether compensation has an effect on the performance of the Bengkulu City Fire and Rescue Service employees. In this research, the type of research is quantitative, which means the type of research based on the philosophy of positivism, is used to examine certain populations or samples. The population in this study were employees of the Bengkulu City Fire and Rescue Service and the sampling technique used in this study was purposive sampling. The number of respondents in this study were 110 employees of the Bengkulu City Fire and Rescue Service. Methods of data collection using a questionnaire. By using multiple linear regression analysis technique, the results of this study can be concluded that the job training variable has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance.